2015
DOI: 10.1007/5584_2015_139
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite in Sarcoidosis: Relation to Mycobacterium Stationary Phase

Abstract: There is evidence that the same mycobacterial heat shock proteins (Mtb-HSPs), especially HSP16, the main marker of mycobacteria dormant stage, occur in sarcoid tissues and in circulated immune complexes and prompt the immune responses against the different genetic background, leading to the development of acute sarcoidosis (SA)/Löfgren syndrome, chronic SA, latent tuberculosis (TB), or active TB. In SA there is increased monocytes phagocytic activity, decreased clearance of antigens/immune complexes by monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Opinions differ on the exact mechanism, but it has been suggested that sarcoidosis is caused by immune reactivity against incompletely degraded and persisting bacterial antigens, rather than a conventional infection [43]. Mycobacterial and propionibacterial DNA and protein have been identified in sarcoidosis granulomas, and several studies show reactivity of lung-derived T-cells to mycobacterial proteins [4], most frequently mycobacterial catalase-peroxidase (mKatG), the 6-kDa early secretory antigenic target (ESAT-6) and heat-shock proteins [44,45]. Broad-spectrum anti-mycobacterial therapy has demonstrated positive effects on lung function in chronic sarcoidosis patients [46], although this was primarily attributed to anti-inflammatory effects rather than specific pathogen eradication [47].…”
Section: Sarcoidosis Results From Immune Hyperactivitymentioning
confidence: 99%
“…Opinions differ on the exact mechanism, but it has been suggested that sarcoidosis is caused by immune reactivity against incompletely degraded and persisting bacterial antigens, rather than a conventional infection [43]. Mycobacterial and propionibacterial DNA and protein have been identified in sarcoidosis granulomas, and several studies show reactivity of lung-derived T-cells to mycobacterial proteins [4], most frequently mycobacterial catalase-peroxidase (mKatG), the 6-kDa early secretory antigenic target (ESAT-6) and heat-shock proteins [44,45]. Broad-spectrum anti-mycobacterial therapy has demonstrated positive effects on lung function in chronic sarcoidosis patients [46], although this was primarily attributed to anti-inflammatory effects rather than specific pathogen eradication [47].…”
Section: Sarcoidosis Results From Immune Hyperactivitymentioning
confidence: 99%
“…Long-term Mtb-HSP16 stimulation also reduces mononuclear phagocyte apoptosis [ 16 , 18 , 41 , 49 , 51 , 54 , 55 , 56 , 57 ].…”
Section: Concentration Of Nitrates/nitrites (Nox) In the Blood Serum ...mentioning
confidence: 99%
“…Since NOx reduction can also result from the reaction of NOx with peroxide and the subsequent production of ONOO − , Dubaniewicz et al [ 54 ] assessed peroxynitrite levels in supernatants of Mtb-HSP-induced PBMC cultures from the same research groups ( Figure 3 ). Significantly higher concentrations of ONOO − with Mtb-HSP stimulation were found in patients with SA and tuberculosis than in the control group.…”
Section: Concentration Of Peroxynitrite (Onoo − ) ...mentioning
confidence: 99%
See 1 more Smart Citation